Motivation Of Planters In Conducting Castration In Crops Not Yet Producing Palm Oil In Bandar Island District Asahan District - Arman, Iman; Siahaan, Wahyuni; Novita, Aisar (JASc (Journal of Agribusiness Sciences), 2023)
The purpose of this study was to determine the level of motivation and factors that influence planters in performing castration on TBM. This research was conducted in Bandar Pulau District, Asahan Regency from April to June 2023. The data collection method used was observation and interview using a questionnaire that had been tested for validity and reliability, while the data analysis method used a Likert scale and multiple linear regression. The results showed that the level of farmer motivation was 84%. Further testing using the t test showed that the farming experience factor, income, External Knowledge, and the availability of farm business credit had a significant effect while the age and education factors did not have a significant effect with the t value greater than the t table.